Quality Education in the Hospitality Industry: Its Impact on Sustainable Tourism in Central Java - Arya Dirgantara; Waluyo Pambudi (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2025)
The growth of the tourism industry in Central Java, bolstered by product development and hospitality infrastructure, is highly dependent on the quality of its human resources. This research aims to investigate the impact of quality education in the hospitality industry on the sustainability of tourism in Central Java. The novelty of this study lies in its comprehensive integration of the Competency-Based Curriculum (CBC) for hospitality with the pillars of sustainable tourism (economic, social, environmental) within an analytical framework that focuses on the regional characteristics of Central Java. The findings indicate that CBC significantly enhances graduate employability through the mastery of technical skills, while also equipping them with the mindset and capacity to implement eco-friendly practices (green hospitality), preserve local culture, and manage economic impacts sustainably. Furthermore, factors such as the application of corporate image practices, social media development, and government program support also contribute to industry growth. This study concludes that strategic investment in adaptive and high-quality vocational hospitality education, supported by multi-sectoral partnerships, is an essential catalyst. This is crucial not only for improving graduate readiness for work and competitiveness but also for supporting responsible, inclusive, and long-term tourism growth in Central Java, aligning with the achievement of Sustainable Development Goal Target 4.4 (SDG 4.4) and promoting social justice.